Vulnerability of the elderly to sexually transmitted infections - Andrade, Juliane [UNESP]; Ayres, Jairo Aparecido [UNESP]; Alencar, Rubia Aguiar [UNESP]; Cassamassimo Duarte, Marli Teresinha [UNESP]; Garcia de Lima Parada, Cristina Maria [UNESP] (Univ Fed Sao Paulo, Dept Enfermagen, 2017)
Objective: To identify the prevalence and factors associated with sexually transmitted infections (STIs) among the elderly. Methods: Cross-sectional study was conducted in a municipality of Sao Paulo from 2011 to 2012. A structured questionnaire was administered to 382 elderly people, and their blood samples were collected to test for syphilis, hepatitis B, and HIV/AIDS. Data were analyzed using the logistic regression model, with discussion based on the benchmark of vulnerability. Results: The prevalence of STIs was 3.4%, with 2.6%, 0.5%, and 0.3% prevalence of syphilis, hepatitis B, and HIV infection, respectively. Sex and a history of STIs were independently associated with this outcome: women had 12 times more likely to contract STIs than men, and the elderly with a history of these infections were 5 times more likely to contract an STI than those without a history of these infections. Conclusion: The results indicated individual and programmatic vulnerabilities of the elderly to STIs. It is essential to suggest strategies that encourage women to negotiate safe sex practices as well as educating healthcare professionals on this subject.
Keywords: Sexually transmitted diseases; Vulnerability; Aged; Health of the elderly